2016
DOI: 10.1016/j.ajic.2016.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus, diphtheria, and acellular pertussis vaccination among women of childbearing age—United States, 2013

Abstract: The incidence of pertussis in the United States has increased since the 1990s. Tdap vaccination of pregnant women provides passive protection to infants. Tdap vaccination is currently recommended for pregnant women during each pregnancy, but coverage among pregnant women and women of childbearing age has been suboptimal. Data from the 2013 BRFSS and 2013 NHIS were used to determine national and state-specific Tdap vaccination coverage among women of childbearing age by self-reported pregnancy status at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Prenatal Tdap immunization also varied regionally, which is consistent with national survey data on Tdap immunization among women regardless of pregnancy status. 29,30 Specifically, prenatal Tdap receipt was highest in the Midwest and lowest in the South. Racial disparities in vaccine receipt may partially explain the geographic distribution, as Black women are less likely to receive prenatal Tdap compared to White women.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal Tdap immunization also varied regionally, which is consistent with national survey data on Tdap immunization among women regardless of pregnancy status. 29,30 Specifically, prenatal Tdap receipt was highest in the Midwest and lowest in the South. Racial disparities in vaccine receipt may partially explain the geographic distribution, as Black women are less likely to receive prenatal Tdap compared to White women.…”
Section: Discussionmentioning
confidence: 99%
“…While urbanicity has not been previously reported as a risk factor for maternal vaccination, it may be a proxy for factors that we could not measure in this study, such as race/ethnicity, income, and access to care, which have previously been associated with Tdap and influenza vaccination among pregnant women and Tdap vaccination in women of childbearing age. 18,33,34 A similar recent study by Butler and colleagues using the Marketscan database found that prenatal Tdap vaccination increased from 9.8% among women who delivered in October 2012 to 44.4% among women who delivered in December 2014. 20 Our study provides a more complete examination of the impact of ACIP's revised Tdap recommendations, including two additional years of data in the post-2012 period and more detailed breakdowns of vaccination prior to 27 weeks gestation.…”
Section: Discussionmentioning
confidence: 86%
“…1 We estimated the incidence of persisting protection from prepregnancy vaccination by combining the proportion of women of childbearing age who reported being vaccinated in the past 12 years with the average vaccine efficacy against pertussis over a 12-year period. 19,20 We used the annual rate of pertussis infection in unvaccinated people aged 15-65 years to approximate the rate of infection in the unvaccinated strategy. 16 We used the CDC's 2017 Pertussis Surveillance Report to determine the rate of pertussis in 0-1 year of life, as well as the rates of hospitalization and death.…”
Section: Methodsmentioning
confidence: 99%